Firm ownership and enterprise risk management implementation: Evidence from the Nordic region - Naciye Sekerci; Don Pagach (Journal of Risk and Financial Management, 2020)
The purpose of this paper is to investigate whether firm ownership characteristics can explain demand for Enterprise Risk Management (ERM) implementation. Specifically, we examine the relationship between the presence of large shareholders, multiple blockholders and a dual-class share structure, and ERM implementation. To our knowledge we provide the first evidence on the effect of multiple blockholders and dual-class share structures on the implementation of ERM. ERM best practices can be considered as governance tools, used to monitor managerial discretion in risk management, ultimately reducing the agency cost of risk management. Accordingly, we analyze the demand for ERM in certain governance (e.g., ownership) settings. We use quantitative methods in our study: survey and regressions (tobit and logit models). Ownership data is hand-collected while ERM data comes from a survey conducted in the Nordic region. We find that ERM is implemented less frequently in firms where there are multiple blockholders, and where large controlling owners hold dual-class shares. These findings indicate that there is less demand for ERM's monitoring role in firms that are associated with high agency costs. Given the increasing use of dual-class share structures, we believe further examination of ownership characteristics and corporate risk management is warranted.
Keywords: 330; agency cost; dual-class shares; Enterprise Risk Management; large owners; multiple blockholders; ownership structure